IDENTIFIKASI BAKTERI PADA SPUTUM PASIEN PENYAKIT PARU OBSTRUKTIF KRONIS EKSASERBASI AKUT DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Nora Aries Marta; Fauzia Andrini; Azizman Saad (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Chronic Obstructive Pulmonary Disease is characterized by persistent airflow limitation, progressive, associated with chronic inflammatory response caused by noxious particles and gases. The severity of COPD depends on its exacerbations and comorbidities of each individual. One of the most factors cause exacerbation of COPD is bacterial infection. The purpose of this study was to know the percentage of bacterial infection cause the exacerbation and the pattern of its etiologic bacteria. The samples were sputum of hospitalized patients with exacerbation of COPD in the Lung room RSUD Arifin Achmad Riau Province. The sputum specimen was collected using sterile containers and subjected to Gram’s stain, culture and biochemical reactions. This study obtained 100% of sputum cultur for pathogenic bacteria was possitive in all 23 cases. The most etiologic bacteria were gram negative 83% which is Klebsiella sp. as the leading bacteria 48%, followed by Acinetobacter sp. 22% and Enterobacter sp. 13%. Gram possitive Staphylococcus aureus were found about 17% in exacerbation of COPD. Keywords : COPD, exacerbation, bacterial identification